The Impact of ICT Acquisition, Online courses, and Management System on Cultural Differences and English Language as Related to the Moderator Effort Expectancy: A Case Study at EPU - Bnar Abdulmajeed Ghafour; Shirzad Mohammed Mahdi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study was conducted to discover the connection between the use of ICTs and English language achievement of students at EPU. The objectives of the study are to study the relationship between the use of ICTs and English language achievement of freshmen level students. The population of the study included all the students which are enrolled in first stage of all department colleges at ERBIL Polytechnic university in Iraq-Kurdistan. The sample of the study comprised 209 students including 111 females and 98 males. The data was collected by a self-developed questionnaire which was based on the students’ opinions related to the use of ICT. All the 209 students answered the questions of four-point Likert type questionnaire that had 15 items. Data were collected from first stages students (both male and female) of three colleges that include numerous departments. The data gathered from the students were analyzed on IBM SPSS Amos and SPSS. Standard deviation was calculated to find the major results. The study found the benefits and major roles of ICT in education sector specifically in learning English language in class and online classes during the pandemic COVID19. Also explored that ICT helps student to obtain management system; students’ performance, quality, capability and value.